MANHAJ TAFSIR AL-KHAZIN (Lubab al-Ta’wil fi Ma’ani al-Tanzil) - Ra'fah Jamilah Saadah (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
AbstractInterpretation is the work of man and the result of his understanding of the Divine Kalam. Interpreting the Qur'an means that humans try to capture the ideas and meanings contained in the verse. Because it is the work of humans, the interpretation of al-Qur'an is always colored by their exegetical thoughts, their comments and comments on a verse are the manifestations of what is in their minds. Even more than that, that interpretation of a verse is colored by the school he adheres to. A mufassir who always struggles and engages in exact sciences or is very interested in studies about the science, for example, interpreting the al-Qur'an verses from aspects of science so that their interpretations are always associated with modern scientific theories. Likewise the mufassir who embrace the Mu'tazilah school of thought, their interpretations are always colored by Mu'tazilah's thoughts.Because interpretation is a human work which is always colored by thoughts, schools, and disciplines that are pursued by the exegetes, the books of interpretation have various styles of thought and schools.